Pengembangan Media Digital STEM Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Pada Materi Hukum Archimedes - Rahardhian, Adhitya; Astuti, Indri; Maria, Haratua Tiur (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
Critical thinking as 21st-century skill is important, but students' low critical thinking skills are a problem that is often found. This study aims to develop STEM digital media to improve students' critical thinking skills on Archimedes' principle. The subjects of this research included 15 validators and 42 students of SMP Negeri 2 Balai. This type of research is Research & Development (R&D) with nine steps of the Dick, Carey, & Carey instructional model. Product validation results show Aiken's V average in the design, media, and material aspects of 0.85; 0.93; and 0.89 so that the media is declared valid in each aspect. The results of formative evaluation in one-to-one evaluation, small group evaluation and field trial evaluation are categorized as very good. The N-gain value from the pretest and posttest is known to be 0.36 (moderate). The effect size of media is 2.44 (high). The implication of this research is the STEM approach combined with digital media has a positive influence on students' critical thinking skills.